Online Learning Readiness. Issue 3 (2nd July 2020) - Joosten, Tanya; Cusatis, Rachel
ABSTRACT: This paper examines the relationship between student characteristics of online learning readiness and student outcomes in online courses at two higher educational institution. Data were collected from student surveys (student characteristics of readiness and outcomes) and merged with institutional student information systems data (e.g., demographics and course grades). Multiple regression analyses revealed that several student characteristics of online learning readiness significantly influenced student outcomes. MANOVA analyses were conducted to examine between group differences of each student characteristics among underrepresented student groups. Significant findings are reported for minorities and for students with disabilities.